Pengetahuan Anak Kebutuhan Khusus Mencuci Tangan 6 Langkah Dengan Benar Pakai Sabun - Mariyana, Rina; Febrina, Cory (Universitas Fort De Kock Bukittinggi, 2021)
Background: Children are susceptible to diseases, especially infectious diseases. According to data, 10% of child deaths are due to diarrhea. Children with special needs are poorly informed about how to wash their hands in an appropriate manner. Washing hands using soap can reduce the transmission of the disease. Motivation of children with special needs in washing hands needs to be increased. The purpose of this study was to see the relationship between children's knowledge in washing hands and the ability of children to wash their hands in 6 steps properly and correctly in special schools (SLB) Bukittinggi 2020. Methods: This study used the chi square test, on 34 respondents. Results: The results of this study obtained low knowledge of children (73.5%) of respondents and low ability (70.6%) of respondents with p-value = 0.000. Conclusion: The conclusion is that the ability to wash the hands of children with special needs is still categorized as low with minimal implementation intervention. Therefore it is recommended to do hand washing socialization in the right steps. Keywords: Children, Special Needs, Handwashing Hand, Knowledge